The Effect of Work Family Conflict on Employee Performance with Mediation of Work Stress (Case Study on Ari Firm-Wooden Crafts Exporter) - Arsania, I Wayan Gde; Supartha, I Wayan Gede (Technium Social Sciences Journal, 2020)
Employees who have domestic work often conflict with family interests and work requirements. The purpose of this study was to analyze the effect of family conflict on work stress and improved performance on companies improving the Ari Firm. In addition, it is also to analyze work stress as a mediator on the effect of work family conflict on improving the performance of Ari Firm. The research was conducted on 154 Ari Firm’s employees who are married. The research instrument used was a questionnaire that had submitted validity and reliability. The collected data is then analyzed using the SEM-PLS technique. The analysis shows that family conflict has a positive and significant effect on work stress, meanwhile work family conflict has negative but no significant effect on employee performance. In addition, work stress has also been proven to mediate the significant influence of family conflict on employee performance.